REFLECTIONS BY JOHN PAUL II AND BENEDICT XVI TOWARDS THE EUROPEAN UNION - Pavilionis, Žygimantas (Politologija, 2015)
John Paul II and Benedict XVI have brought Catholic Church back to international arena after the shock of Enlightenment in XVII century. They had an important impact on reemergence of united Europe by the end of XX century. Unfortunately in the beginning of XXI century modern functionalist European Union symbolically rejected any reference to its Christian roots, unveiling deep moral drama of current establishment of the European Union. The European Union has lost its meta-political level, its spiritual vision, its mission, at the same time it has lost the link to human dignity, to the spiritual mission of its own citizen and their nations. By rejecting the reference to Christian roots the European Union has rejected its own future.